Acute Effects of Low-Load/High-Repetition Single-Limb Resistance Training in COPD. Issue 12 (December 2016) - NYBERG, ANDRÉ; SAEY, DIDIER; MARTIN, MICKAËL; MALTAIS, FRANÇOIS
ABSTRACT: Exercising small muscle groups at a time allows higher muscle specific workloads compared with whole body aerobic exercises in people with chronic obstructive pulmonary disease (COPD). Whether similar effects also occur with partitioning exercise during low load/high-repetition resistance exercises is uncertain. Purpose: To investigate the acute effects of partitioning exercise on exercise workload, exertional symptoms and quadriceps muscle fatigue during low load/high-repetition resistance exercises in people with COPD and healthy controls. Methods: We compared the acute physiological effects of single-limb (SL) versus two-limb (TL) execution of isokinetic knee extension and of six low load/high-repetition elastic resistance exercises in 20 people with COPD (forced expiratory volume in 1 s = 38% predicted) and 15 healthy controls. Results: Among people with COPD, SL exercises resulted in higher exercise workloads during isokinetic knee extension (17% ± 31%, P < 0.05) and elastic exercises (rowing, 17% ± 23%; leg curl, 23% ± 21%; elbow flexion, 19% ± 26%; chest press, 14% ± 15%; shoulder flexion, 33% ± 24%; and knee extension, 24% ± 18%, all P < 0.05). Muscle fatigue ratings were similar during SL compared with TL exercises, whereas dyspnea ratings were similar between conditions during isokinetic exercises and lower during SL compared with TL elastic exercises ( P < 0.05). In COPD, SL knee extension resulted in greater quadriceps fatigue than TL knee extension as evidenced by a greater fall in quadriceps potentiated twitch force after the former exercise (−24% ± 10% vs −16% ± 8%, P = 0.025). In healthy controls, partitioning exercise with SL exercise did not modify workload, quadriceps fatigue nor dyspnea achieved during the various exercises. Conclusions: Partitioning exercise by exercising using an SL allowed higher muscle localized exercise workloads, larger amount of quadriceps muscle fatigue with lower, or similar level of exertional symptoms during low load/high-repetition resistance exercises in people with advanced COPD.